THE EFFECT OF USING PQ4R METHOD ON STUDENTS ABILITY IN READING COMPREHENSION AT EIGHT GRADE OF SMP N 3 SATU ATAP PANGKALAN SUSU - Hayati, Mala (Faculty of Tarbiyah nad Teacher Training, 2021)
This study aims to determine the effect of using PQ4R method on students’ reading comprehension. The subject of this research was students of SMP N 3 Satu Atap Pangkalan Susu at eight grade. This research were used quasi experimental with pre-test and post-test design. In this design there was two groups, namely groups randomly selected experimental and control groups. The researcher were use two classes as sample in this research, they were VIII A that consisted of 30 students of experimental class and VIII B that consisted of 30 students of controlled class, namely class VIII A was an experimental class and given action was used the PQ4R method and class VIII B was controlled class in this study given used conventional method. This research were used quantitative method. The findings of this study that t-observed (3.79) was higher than t-table (1.674) at the level of significance ofα = 0.05and at the degree of freedom (df) = Nx + Ny – 2. Where Nx the total numbers of Experimental class is 30 and Ny was the total numbers of control class is 30. Thus, df = 30 +30- 2= 58. Based on the data, it can be concluded that there was a significant effect between using PQ4R method and conventional method on the students’ achievement in reading comprehension.Keywords: PQ4R Method, Students’ Reading Comprehension, Experimental